Analisis Sentimen Menggunakan Support Vector Machine Sebagai Tools Evaluasi Layanan Sipraja Mobile - Affandi Trihusada, Muhammad (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2025)
E-government is one of the government's strategies to implement good governance through the use of technology to improve public services. The realization of e-government is done through the provision of web-based and mobile services by the Sidoarjo Government by releasing the Sidoarjo People's Service System (Sipraja). Sipraja is an application that integrates administrative services in villages and sub-districts. Sipraja mobile has been downloaded by more than 100,000 users, received more than 2,000 reviews, and received a review rating of 4.2. However, user review ratings sometimes do not match the format of the review text provided. This study aims to get an overview of public perceptions / sentiments towards Sipraja mobile services to be used as evaluation material. Research was conducted to analyze user reviews of the Sipraja mobile application on Google Playstore using the Support Vector Machine (SVM) algorithm and linear kernel type. The research model used is able to produce an accuracy rate of 75.10%, precision of 80.36%, specificity 81,97%, recall of 68.70% and F1 score of 74.07%. From the research results, public sentiment towards Sipraja mobile services is more inclined to positive sentiment of 54.84% However, negative sentiment has a similar amount of 45.16%. The Sidoarjo local government's attention and follow-up is needed to continue to meet the objectives of e-government to improve services to the community.